MAXONFORM IS A FREE-FORM MODELLING APPLICATION THAT ENABLES THE USER TO CREATE ANY SHAPE. - Dobson, Bernard (Architects' Journal, 2005)
The article presents a birds eye view of the author that relates to switching of the computer design software. First reason of switching another software is that Computer Aided Design, after 15 years the Advanced Developer's Toolkit was becoming complicated to use and he wants to work in a single model environment.